2014
DOI: 10.1902/jop.2014.130635
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Periodontal Ligament Cells to Baicalin

Abstract: Baicalin showed multifaceted regulation of genes with important roles in tissue growth and differentiation, and thus it has the potential to be a promising candidate for HPLC-based periodontal regeneration therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Baicalin has been used for the treatment of ulcerative colitis [14], endotoxemia [15], periodontitis [16] and various inflammatory diseases [17,18]. Other studies have shown that baicalin promotes human periodontal ligament cell (HPLC) proliferation, reduces the ratio of receptor activator of nuclear factor-kappaB ligand (RANKL) to osteoprotegerin (OPG) expression [19], cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) activity [16], interleukin-6 (IL-6) and IL-8 expression [20], and protects against tissue damage in animal models of periodontitis [16]. Although baicalin inhibits TLR4 activation in human oral keratinocytes [20], however, it is still unclear whether baicalin can regulate TLR2 and TLR4 expression and relevant signaling in a rat model of experimental periodontitis.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Baicalin has been used for the treatment of ulcerative colitis [14], endotoxemia [15], periodontitis [16] and various inflammatory diseases [17,18]. Other studies have shown that baicalin promotes human periodontal ligament cell (HPLC) proliferation, reduces the ratio of receptor activator of nuclear factor-kappaB ligand (RANKL) to osteoprotegerin (OPG) expression [19], cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) activity [16], interleukin-6 (IL-6) and IL-8 expression [20], and protects against tissue damage in animal models of periodontitis [16]. Although baicalin inhibits TLR4 activation in human oral keratinocytes [20], however, it is still unclear whether baicalin can regulate TLR2 and TLR4 expression and relevant signaling in a rat model of experimental periodontitis.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Furthermore, baicalin inhibited the pro-inflammatory gene expression via down-regulating the TLRs/NF-κB signaling, such as COX-2, iNOS, TNF-α , IL-6, IL-13 and HMBG-1 in cervical tissue and colon tissue [11,30,32]. In addition, baicalin inhibited the production of IL-1β, IL-8, PGE2, leukotriene B4 (LTB4), COX-2, RANKL/OPG ratio, and inhibited the NF-κB, p38 MAPK in many types of cells involved in the process of periodontitis, such as human gingival fibroblasts, periodontal ligament cells, oral keratinocytes and cultured osteoblasts [19,20,[34][35][36]. In our study, baicalin down-regulated of HMGB1, TNF-α, IL-1β, and MPO in gingival tissues by down-regulating the TLR2 and TLR4/MyD88/ NF-κB signaling, and reduced inflammatory infiltrates and MPO production possibly by affecting these types of inflammatory cells during the process of periodontitis.…”
Section: The Pharmacological Effects Of Baicalinmentioning
confidence: 99%
“…27,28,30 Previous evidence has demonstrated that BA showed desirable effects against periodontitis and alveolar bone resorption and it exerts these effects by inhibition of the RANKL mRNA expression and upregulation of the NF-κB activation. 5,29,30,43 Other than, BA was proved to increase the osteoblastic mineralization and promote osteoblastic differentiation via Wnt/β-catenin signaling. 31 However, the effects of BA on osteoporosis and the mechanisms by which it exerts these effects remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In human periodontal ligament cells, BA upregulates OPG expression and downregulates RANKL expression. 29,30 Additionally, BA has also been found to enhance the mRNA expression of OPG and promote osteoblastic differentiation via the Wnt/β-catenin signaling pathway. 31 These encourage findings hint that BA might regulate the activity of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…Outro fator importante para diferenciação dos osteoblastos, a osteocalcina, apresentou elevada expressão de RNAm em culturas de células do ligamento periodontal humano tratadas com Baicalin (componente com propriedade antimicrobiana e anti-inflamatória) (Pei et al, 2014). Tendo conhecimento de que receptores tipo NLRs participam da cronificação do processo inflamatório, paralelamente ao trabalho citado anteriormente, podemos verificar que a ausência dos receptores NOD1 e NOD2 também promoveu uma inclinação ao aumento da expressão gênica de osteocalcina.…”
Section: W83unclassified